A Retrospective Study of Neonatal Outcome in Preeclampsia at the University Hospital of the West Indies: A Resource-limited Setting. (24th March 2018) - McKenzie, Kerri-Ann; Trotman, Helen
Abstract: Aim: This study aimed to determine the outcome of neonates born to women with preeclampsia at the University Hospital of the West Indies (UHWI). Methods: This was a retrospective descriptive study looking at the outcome of all babies born to women with preeclampsia and control babies born to normotensive women at the UHWI over a 20-month period. Maternal and neonatal demographic data and course of admission for admitted neonates were recorded. Descriptive analyses were performed. Results: Neonates born to women with preeclampsia were more likely to be low birth weight [odds ratio (OR = 2.8; confidence interval (CI): 2.2–3.5], small for gestational age (OR = 2.3; CI: 1.9–2.9) or premature (OR = 2.5; CI: 2.0–3.0). They had a lower mean 5 min Apgar score than babies born to normotensive women p <0.05. They were also more likely to be admitted to the neonatal unit 67 (59%) compared with neonates of normotensive women 13 (13%) p <0.001. The main reason for admission was prematurity. Eighteen neonates, all born to women with preeclampsia, died, and the main cause of death was prematurity. Conclusion: Adverse neonatal outcome was noted in neonates born to women with preeclampsia, and this was predominantly related to prematurity and its complications.